In vitro antioxidant properties and antimicrobial activity of the ethanolic extract of Senecio nutans Sch. Beep. (Asteraceae) - Felipe Surco-Laos; Jorge A. Garcia; María R. Bendezú; Doris Laos-Anchante; Juan F. Panay-Centeno; Manuel Valle-Campos; Juan J. Palomino-Jhong; Paulina Eliades Yarasca-Carlos; Berta Loja; Angel T. Alvarado (GarVal Editorial Ltda., 2022)
Context: Senecio nutans Sch. Beep. is used by the Andean population of Ayacucho-Peru as traditional medicine for various health problems. Aims: To evaluate the antioxidant and antimicrobial activity of the ethanolic extract of leaves of S. nutans against the enteropathogen Escherichia coli and the filamentous fungus Aspergillus niger. Methods: The antioxidant capacity of the ethanolic extract was evaluated by ABTS, DPPH, and FRAP assays; the antimicrobial activity was evaluated by the agar diffusion method, and determining the minimum inhibitory concentration (MIC), minimum bactericidal (MBC), and fungicidal concentration (MFC). Results: Polyphenols, terpenes, and tannins were identified; the total polyphenolic content was 67.91 ± 0.29 mg GAE/g. The ethanolic extract at 20 mg/mL showed moderate antibacterial activity (79.14 ± 0.02% inhibition, MIC and MBC >400 μg/mL on E. coli), and antifungal (88.90 ± 0.17% inhibition, MIC and MCF >400 μg/mL on A. niger); radical scavenging capacity (ABTS 10.31 ± 0.09 mM TE/g; DPPH 8.28 ± 0.07 IC50 µg/mL) and iron reducing power (FRAP 17.72 ± 0.11 mM TE/g). S. nutans turned out to be a potential antimicrobial and antioxidant species associated with the presence of its bioactive components, for which further investigation is warranted. Conclusions: The ethanolic extract of leaves S. nutans showed moderate activity against pathogenic bacteria (E. coli) and filamentous fungus (A. niger), as well as antioxidant activity in three in vitro methods.